Sa aking pagkakagising mula sa kamulatan (awaken) - Aquino, Carlo; Eusebio, Ketchup; Macaso, Hector
A realistic glimpse of the Filipino youth in the gulf of Manila's urban gullies that tackles socially-related issues surrounding the intersecting lives of marginalized ordinary Manileños. Presented in a staggered vista of correlated events, the movie explores the day-to-day survival of the characters and their broken dreams, pent-up anger and abnormal sexuality. It conveys its message powerfully in a daring and unapologetic way-- using street lingo to it's fullest. The story unfolds one night when Rey, the docile and cowardly teenage student is mauled as he passes by a drinking spree of street toughies: Pogie, Jopet, Kahoy and Taba.